‘Techno mums’ motivations towards vegetarian and vegan lifestyles - Mortara, Ariela (Italian Sociological Review, 2013)
In the last few years, food related issues have become highly relevant in private and public discourses; along with the increased interest in food safety, both vegetarianism and veganism have enlarged their popularity and acceptance. The general concern toward the consumption of healthy food should be even more important for the mothers wanting to provide safe food for their children and therefore adopting alternative lifestyles such as vegetarian and vegan diets. However, the literature regarding the vegetarian and vegan choices does not focus on the motivations fostering mothers toward these lifestyles. This paper tries to fill this gap presenting the results of a study aimed at investigating the motivations underlying the adoption of vegetarian and vegan lifestyles. Such motivations emerge from the online dialogs among a very specific sample of mothers, the so called ‘techno mums’.